2020
DOI: 10.3389/fonc.2020.606380
|View full text |Cite
|
Sign up to set email alerts
|

Wilms Tumor in Sub-Saharan Africa: Molecular and Social Determinants of a Global Pediatric Health Disparity

Abstract: Wilms tumor (WT) is the most common renal malignancy of childhood. Global disparities in WT have been reported with the highest incidence and lowest overall survival occurring in sub-Saharan African nations. After a detailed search of PubMed, we reviewed available literature on WT in sub-Saharan Africa and summarized findings that explore biologic and social factors contributing to this alarming cancer health disparity. Access to care and treatment abandonment are the most frequently reported factors associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In this study, renal tumors were the most common diagnosis (32.4%), 19 with patients with leukemia accounting for 20.5% of all oncological patients admitted. This is in keeping with statistics that black children in Sub-saharan Africa have the highest incidence of Nephroblastoma worldwide.…”
Section: Discussionmentioning
confidence: 76%
“…In this study, renal tumors were the most common diagnosis (32.4%), 19 with patients with leukemia accounting for 20.5% of all oncological patients admitted. This is in keeping with statistics that black children in Sub-saharan Africa have the highest incidence of Nephroblastoma worldwide.…”
Section: Discussionmentioning
confidence: 76%
“…A total of 7347 articles were not selected during the database search stage because they did not meet the inclusion criteria. Two duplicates were removed, leaving 64 articles which were screened for abstracts [ 13 – 74 ]. A total of 25 articles were removed at the abstract screening stage because they formed part of the exclusion criteria (i.e., those conducted outside of SSA, those with no relevant outcomes for the study, those not in the specified age group, and those which are not primary studies).…”
Section: Resultsmentioning
confidence: 99%
“…While one must acknowledge social, structural and cultural barriers responsible for this dismal overall survival in developing countries, a recent review by Apple and Lovvorn in 2020 suggested there may also be an underlying biological and molecular basis that may account for this discrepancy. 5 More research needs to be done to understand Wilms' tumorigenesis in our setting.…”
Section: Discussionmentioning
confidence: 99%